O cuidado com o corpo - Elias, Andréia Bezerra da Silva; Bernardo, Lucia Valério da Silva; Gonçalves, Rosicler da Silva; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf